Ma: entre-espaço da comunicação no Japão um estudo acerca dos diálogos entre Oriente e Ocidente - Okano, Michiko (2007)
The dissertation investigates a few possibilities to translate the Japanese cultural element known as Ma, which represents an inter-space in which and at what time the process of communication occurs. The study starts from the understanding of Ma as a quasi-sign, which in its turn is a concept from Peircean semiotics, recognizable only through its materialization in this case, the Ma spatialities that we discuss on the basis of examples drawn from architecture and the motion pictures. At the end of a comprehensive bibliographical research on the theme, which included Japanese and Western titles, the study describes and examines the exhibition organized by architect Isozaki Arata in Paris, in 1978, that transformed Ma into a symbol of the Japanese culture exported to the West. Subsequently, it presents readings of Ma spatialities found in traditional Japanese architecture as well as in a few works by architect Ando Tadao (1941 - ). As regards examples from the motion pictures, the study has contemplated feature fi lms by classical Japanese motion-picture director Ozu Yasujiro (1903 - 1963) and by moviemaker and actor Kitano Takeshi (1947 - ). Our main objective is to propose the Ma spatiality as both sign and characteristic mediation process of cognition and perception among the Japanese in such a way as to open new possibilities of communication to deepen the dialogue between Japan and the West, outside the exclusive sphere of stereotyped images that are easily accepted by market paradigms in times of globalization